OPTIMIZATION OF IRBESARTAN TABLET FORMULATION BY 23 FACTORIAL DESIGN - Chowdary, K. P. R.; Shankar, K. Ravi; Sowjanya, V. V. L. S. P. (International Journal of Current Pharmaceutical Research, 2015)
Irbesartan, a widely prescribed anti hypertensive drug belongs to class II under BCS classification and exhibit low and variable oral bioavailability due to its poor aqueous solubility. It needs enhancement in the dissolution rate in its formulation development. Complexation with β-cyclodextrin (βCD) and use of Crospovidone and PVP K 30 are tried for enhancing the dissolution rate of irbesartan in its formulation development. The objective of the present study is optimization of irbesartan tablet formulation employing Crospovidone, βCD and PVP K 30 by 23 Factorial design. Formulation of irbesartan tablets with NLT 85% dissolution in 15 min employing Crospovidone, βCD and PVP K 30 was optimized by 23 Factorial design. Eight irbesartan tablet formulations were prepared using selected combinations of the three Factors as per 23 Factorial designs. Irbesartan tablets were prepared by direct compression method and were evaluated for drug content, hardness, friability, disintegration time and dissolution rate characteristics. The dissolution rate (K1) values were analysed as per ANOVA of 23 Factorial design to find the significance of the individual and combined effects of the three Factors (βCD, Crospovidone and PVP K 30) involved on the dissolution rate of irbesartan tablets formulated. The individual and combined effects of βCD, Crospovidone and PVP K 30 on the dissolution rate (K1) of irbesartan tablets are highly significant (P<0.01). Irbesartan tablet formulation (PFac), disintegrated rapidly with in 1 min and gave very rapid dissolution of irbesartan,100% in 15 min. Higher levels of βCD and lower levels of Crospovidone gave low dissolution rates of irbesartan tablets. The increasing order of dissolution rate (K1) observed with various formulations was CFac> CFa>CFab>CFabc> CF1> CFbc> CFb> CFc. The polynomial equation describing the relationship between the response i. e. percent drug dissolved in 15 min (Y) and the levels of Crospovidone (X1),βCD (X2) and PVP K 30 (X3) based on the observed results is Y = 58.57+34.54 (X1) - 1.89(X2) – 3.60 (X1 X2) -1.82 (X3) +1.50 (X1 X3) + 3.13 (X2 X3) - 4.87 (X1 X2 X3). Based on the above polynomial equation, the optimized irbesartan tablet formulation with NLT 85% dissolution in 15 min could be formulated employing Crospovidone at 27.70% of drug content, βCD at 1:4 ratio of drug: βCD and PVP K 30 at 1% of drug content. The optimized irbesartan tablet formulation gave 86.18 % dissolution in 15 min fulfilling the target dissolution set. The dissolution profile of the optimized Irbesartan tablet formulation was similar to that of commercial brand (IROVEL-150). Hence the formulation of irbesartan tablets with NLT 85% dissolution in 15 min could be optimized by 23 Factorial design.